Morphology parameters for rupture in middle cerebral artery mirror aneurysms. (27th February 2020) - Xu, Wei-dong; Wang, Han; Wu, Qi; Wen, Li-Li; You, Zong-qi; Yuan, Bin; Chen, Shu-juan; Wang, Han-Dong; Zhang, Xin
Abstract : Objective: To identify the morphological parameters correlated with the rupture of middle cerebral artery (MCA) aneurysms. Methods: We retrospectively analyzed the digital subtraction angiography (DSA) data of 48 patients with ruptured mirror MCA aneurysms. Morphological parameters included aneurysm with wall protrusion, maximum diameter (Dmax), height, neck width, aneurysm width, dome projection, parent artery average diameter (Dp), aspect ratio (AR), bottleneck factor (BNF), size ratio (SR), M1/M2 ratio, and height/width (H/W) ratio. These paired parameters were analyzed by conditional univariate and multivariate logistic regressions to screen out the independent risk factors. We established a score based on the independent risk factors. Receiver operating characteristics (ROC) were generated to estimate the prediction performance of the score in our large database of 763 aneurysms. Results: In the univariate regressions, Dmax, height, aneurysm width, neck width, AR, BNF, H/W ratio, SR, anterior dome projection and aneurysm with wall protrusion were significant risk factors. Aneurysm width (OR 3.296, p=0.015), AR (OR 11.594, p=0.014) and anterior dome projection (OR 9.385, p=0.016) were independent risk factors in multivariate regression. The area under the curve (AUC) value of the score based on the three independent risk factors was 0.829. Conclusion: Aneurysm width, AR and anterior dome projection were independent risks factors of rupture.